Prolonged larval development in the Critically Endangered Pehuenche's frog Alsodes pehuenche: Implications for conservation - Corbalán, Valeria Elizabeth (2014)
Overwintering is an anuran strategy to survive in cold-temperate climates. Those aquatic species that withstand harsh conditions and short growing seasons are candidates for having long larval periods. Prolonged larval development, which includes overwintering for more than two years, has been reported for North-American and Euro-Asiatic species, but this strategy has been poorly studied in the Southern Hemisphere. Alsodes pehuenche is an endemic frog from the high Andes mountains of Argentina and Chile, recently categorized as Endangered by the Asociación Herpetológica Argentina (AHA) and as Critically Endangered by the International Union for Conservation of Nature (IUCN). We studied egg laying in this species and its larval development by marking tadpoles with elastomers. We found that eggs are laid in clumps at the beginning of summer. The larval cycle includes four winters, although a fifth winter should not be ruled out. This is the first study that demonstrates a long larval development (four winters) in South-American species and has important implications for conservation biology.